ORDINASI SUNGAI PADOLO BERDASARKAN KOMUNITAS MAKROZOOBENTHOS SEBAGAI BIOINDIKATOR KUALITAS LINGKUNGAN SUNGAI DI KOTA BIMA NTB - , SRI HANDAYANI, S.Pi. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research of the utilization assessment of macrozoobenthos communities as indicator of water pollution have been carried out in Padolo River Bima City. Objectives of research were (1) investigate the relationship between makrozoobenthos communities were found with ecological factors